Stigma and prejudice: one animal or two? - Phelan, Jo C; Link, Bruce G; Dovidio, John F (Social science & medicine (1982), 2008)
In light of increasing cross-communication and possible coalescence of conceptual models of stigma and prejudice, we reviewed 18 key models in order to explore commonalities and possible distinctions between prejudice and stigma. We arrive at two conclusions. First, the two sets of models have much in common (representing "one animal"); most differences are a matter of focus and emphasis. Second, one important distinction is in the type of human characteristics that are the primary focus of models of prejudice (race) and stigma (deviant behavior and identities, and disease and disabilities). This led us to develop a typology of three functions of stigma and prejudice: exploitation and domination (keeping people down); norm enforcement (keeping people in); and disease avoidance (keeping people away). We argue that attention to these functions will enhance our understanding of stigma and prejudice and our ability to reduce them.
Keywords: Continental Population Groups; Health Status Disparities; Humans; Models, Psychological; Power (Psychology); Prejudice; Social Control, Informal; Sociology, Medical; Terminology as Topic